Review of college students' financial knowledge and literacy studies - Sabri, Mohamad Fazli (Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan & Persatuan Ekonomi Pengguna dan Keluarga Malaysia, 2011)
The terms financial literacy, financial knowledge and financial education often are used interchangeably in the literature and popular media (Huston, 2010). Huston (2010) analysed seventy-one individual studies from fifty-two different data sets on broad range of financial literacy or financial knowledge measures where majority of the studies were published between 1996 and 2008. Financial literacy constructs were assessed by whether a definition was provided and whether multiple terms were used to represent the same construct. The majority of studies (72%) did not include the definition of financial literacy. Forty-seven percent of the studies analysed used the terms financial literacy and financial knowledge synonymously. After examining the instrument content (commonality), four main categories emerged: personal finance basics, borrowing, saving/investing and protection. As proposed by Huston (2010), financial literacy could be conceptualised as having two dimensions, which are, understanding personal finance knowledge and using the personal finance knowledge (application). Financial literacy could be defined as measuring how well an individual can understand and use personal finance-related information.